Parents' Perceptions of the Importance of Physical Activity and their Children´S Ability - Vello Hein (Lithuanian Sports University, 2018)
Background. It is well known that parents influence physical activity of their children. Determining the factors related  to  parents'  perception  of  the  importance  of  physical  activity  and  physical  fitness  enables  enhancing  the promotion of physical activity among children in the future. Methods. A total of 237 parents of children aged between 5 and 10 years participated in the study. Confirmatory factor analysis was used to estimate factor structure of the questionnaire "Parents Perceptions of the Importance of Physical Activity and Their Children´s Ability Questionnaire". To investigate the differences between groups Independent-sample t-test was used. Cohen's d was used to estimate effect size. Results. Confirmatory factor analyses showed that the eight-issue two-factorial model psychometric parameters were acceptable in order to assess parents' perception of the importance of physical activity and ability (RMSEA = .072; NFI = .97; CFI = .98; NNFI = .98). Parents who were physically active in the past and were active in the present evaluated the importance of physical activity more than inactive parents. Parents' assessments of the importance of physical activity and ability were not significantly different depending on parents' education, university or secondary/ high education. Conclusion. The questionnaire used is a valid measure of parents´ assessments of the importance of physical activity  and  physical  ability  of  the  Estonian  school  students.  The  questionnaire  enables  us  to  identify  parents' assessments of the importance of physical activity and physical ability, which may be considered as one of the factors related to children's physical activity. Keywords:  parents' evaluations, physical activity, children, confirmation factor analysis